2020
DOI: 10.21203/rs.3.rs-96298/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic and transcriptomic analysis of the thermophilic lignocellulose-degrading fungus Thielavia terrestris LPH172

Abstract: Background: Biomass-degrading enzymes with improved activity and stability can ameliorate substrate saccharification and make biorefineries economically feasible. Filamentous fungi are a rich source of carbohydrate-active enzymes (CAZymes) for biomass degradation. The newly isolated LPH172 strain of the thermophilic Ascomycete Thielavia terrestris has been shown to possess high xylanase and cellulase activities and tolerate well low pH and high temperatures. Here, we aimed to illuminate the lignocellulose degr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(82 reference statements)
1
1
0
Order By: Relevance
“…Our findings suggest that the set of transcripts related to XYR1 and CRE1 varies among the studied T. harzianum strains, suggesting regulatory differences in enzymatic hydrolysis. These findings corroborate previous studies in which differences in biomass degradation and enzyme production between strains of the same species have been reported (de Vries, et al 2017;Thanh, et al 2019;Tolgo, et al 2021). Furthermore, such XYR1 and CRE1 Response to Cellulose Degradation transcripts were not limited to CAZymes and other proteins related to biomass degradation.…”
Section: Xyr1 and Cre1 Response To Cellulose Degradationsupporting
confidence: 92%
“…Our findings suggest that the set of transcripts related to XYR1 and CRE1 varies among the studied T. harzianum strains, suggesting regulatory differences in enzymatic hydrolysis. These findings corroborate previous studies in which differences in biomass degradation and enzyme production between strains of the same species have been reported (de Vries, et al 2017;Thanh, et al 2019;Tolgo, et al 2021). Furthermore, such XYR1 and CRE1 Response to Cellulose Degradation transcripts were not limited to CAZymes and other proteins related to biomass degradation.…”
Section: Xyr1 and Cre1 Response To Cellulose Degradationsupporting
confidence: 92%
“…Secondly, the biodiversity should be spanned, using both enzymes from the well analyzed clades (Figure S4, clades A, B, and C; SI-1) as well as from under-investigated areas of the tree (Figure 1). Thirdly, from our previous transcriptome studies of Malbranchea cinnamomea and Thielavia terrestris (26,27), we have identified two cutinases significantly overexpressed on lignocellulolytic substrates, which were also added to the list. Finally, we added a cutinase from Sirococcus conginenus because of its suggested acid tolerance (19), a trait important in a biorefinery context where pretreatment results in low pH of the biomass slurries (25).…”
Section: Phylogenetic Analysis Of Ce5mentioning
confidence: 99%